PENGELOLAAN PERAIRAN PESISIR GUGUS PULAU KALEDUPA UNTUK USAHA BUDIDAYA RUMPUT LAUT - Akhmad Mansyur; Achmad Fahruddin; Izal Effendi (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
The aim of this study are: (1) the actual condition of the utilization coastal of Kaledupa Islands (CKI), Wakatobi Regency Southeast Sulawesi Province for phycoculture based on the suitability area and the seasons, (2) warranties parameters for optimizing area utilization, (3) the grand utilization strategy of CKI for supporting phycoculture. Suitability analysis, carrying capacity, utilization of regional strategies and optimizes scenario are used for that purpose. The results of this study are showed that 5.946 ha of CKI for supporting phycoculture were categorized to be three areas through good stabile, good dominant and not yet good stabile. The area utilization were showed over limited based on amount of long line unit methods and half of them had been decreasing return to scale. There’s a potential warranties area for Rp 7.246.500 to 12.980.600 per ha per year and Rp 627.612 to 5.785.656 per ha per season for importance rent or contract. The management strategies of CKI are to improve the satisfaction of phycoculturers with the scenario: (1) to repair structures of phycoculture methods, and time period of phycoculture production; (2) to increase user, to compose groups and to reinforce focus groups; and (3) to create guarantee access the capital and to improve input structures of phycoculture